KONSEP KEPEMIMPINAN DALAM ISLAM - Ahmadireja, Bpk (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2014)
Leadership in Islam occupies a very strategic position. Because leadership is an instrument to achieve the lofty ideals of a nation. Namely the creation of a nation that